2008
DOI: 10.4067/s0716-10182008000500010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiología y factores de riesgo de mortalidad de las bacteriemias intrahospitalarias por bacilos gramnegativos

Abstract: Nosocomial bloodstream infections caused by gram-negative bacilli: epidemiology and risk factors for mortality Nosocomial bacteremia is a major cause of hospital infection, associated with high rate of morbidity and mortality, prolonged hospital stay and higher costs. However, few prospective studies analyse the prognostic factors associated with mortality of gramnegative rods bloodstream infections in hospital wards outside of intensive care units. A prospective/descriptive study was conducted from March to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Bacteremia acquired in the hospital is a frequent cause of morbidity and mortality in intensive care units (ICU)], 1 having an important clinical impact on patients’ length of stay and costs associated with health care. 1 , 2 According to the World Health Organization (WHO), 8.7% of hospital acquired infections correspond to bacteremia 2 and retrospective studies have shown that the incidence of nosocomial bacteremia is close to six episodes per 1000 hospital admissions. ICU ranks first amongst hospital services (51% of events) followed by adult internal medicine services (38%), surgical services (20%) and paediatric rooms (13.5%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteremia acquired in the hospital is a frequent cause of morbidity and mortality in intensive care units (ICU)], 1 having an important clinical impact on patients’ length of stay and costs associated with health care. 1 , 2 According to the World Health Organization (WHO), 8.7% of hospital acquired infections correspond to bacteremia 2 and retrospective studies have shown that the incidence of nosocomial bacteremia is close to six episodes per 1000 hospital admissions. ICU ranks first amongst hospital services (51% of events) followed by adult internal medicine services (38%), surgical services (20%) and paediatric rooms (13.5%).…”
Section: Introductionmentioning
confidence: 99%
“…ICU ranks first amongst hospital services (51% of events) followed by adult internal medicine services (38%), surgical services (20%) and paediatric rooms (13.5%). 1 , 2 It has been reported that ICU patients present a greater tendency for developing episodes of nosocomial bacteremia compared to those admitted to different hospital wards. 3 This is related to patients’ susceptibility due to immunosuppression and frequent use of invasive devices, such as intravascular and urinary catheters, and tubes for supporting mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%